Phytoremediation of Hexavalent Chromium Using Aquatic Plants in Nickel Mine Waste - Permatasari, Nur Vita; Abidin, Faizinal; Azmi, Mifta Ulul; Novitasari, Yeni; Hapid, Abdul (BRIN Publishing, 2023)
The abundant wealth that Indonesia has is very profitable. Wealth is not only from natural resources, but wealth or biodiversity is also able to make Indonesia an independent country in managing its environment. One of the varieties that can be utilized is the existence of aquatic plants that can be used in the restoration of polluted environments. The ability of plants to recover from pollutants is called phytoremediation. Hexavalent chromium/ Cr(IV) is a hazardous waste originating from the washing of ore/open pit waste from rainwater washing. The quality standard allowed for Cr (IV), according to the Minister of Environment Regulation No. 9 of 2006, concerning the Quality Standard of Wastewater for Nickel Ore Mining Businesses and/or Activities is 0.1 mg/L. Besides being used to reduce pollutant loads, this aquatic plant can also provide aesthetic value because it has a very beautiful shape, type, color, and flowers. The purpose of this research is to find out which plants can be used to reduce hexavalent chromium levels. Variations of aquatic plants that can reduce levels of hexavalent chromium which are harmful to living things include water hyacinth/Eichornia crassipes; water hyacinth; Kayambang/ Salvinia Cucullata; Kiambang/ Apu Wood/ Pistia Stratiotes; Hydrilla verticillata; Water Bamboo/Equisetum hyemale; Water spinach / Ipomoea Aquatica; and Sagittaria lancifolia. This aquatic plant can reduce Cr (IV) up to 99.5%. The ability of these aquatic plants not only to reduce Cr (IV) but also to reduce TSS, BOD, and COD and to neutralize pH. The combination of several aquatic plants also provides a high effectiveness value.